Analisis Metadata terhadap Tinjauan Literatur Pariwisata Halal - Marsha, Deni; Kharisma Putra, Irfan; Karunia, Erick (Jurnal Manajemen dan Organisasi, 2025)
Halal tourism has grown rapidly in the last decade, along with the increasing interest of global Muslim tourists. This research aims to analyze metadata from halal tourism literature to identify trends, patterns, and academic contributions in this field. Using data from the Scopus database from 2015 to 2025, this research evaluates document distribution based on time, publication type, institutional affiliation, country, and subject area. The findings show that journal articles dominate publications (70.7%), with Business, Management, and Accounting as the main contributor (29.7%). Indonesia and Malaysia emerge as the countries with the largest contributions, reflecting the strategic role of the Southeast Asian region in halal tourism research and development. Theoretically, this research highlights the potential of metadata in integrating tourist preferences, market trends, and destination needs to address challenges such as variations in halal standards, lack of infrastructure, and low public awareness. Practically, these findings offer strategic guidance for governments, industry, and academics to utilize metadata in halal certification, marketing strategies, and digital technology development. The conclusion of this research emphasizes the importance of multidisciplinary approaches and cross-sector collaboration to enhance the appeal and sustainability of halal tourism at the global level. Future researchers are advised to expand the analysis with a more comprehensive interdisciplinary approach.